How does the Problem-Based Learning with Chatbot AI Enhance Learning Outcomes? - Wibowo, Setyo Ajie; Degeng, Made Duananda Kartika; Praherdhiono, Henry; Faizah, Intan (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This study aims to determine the effect of problem-based learning models with chatbot AI on learning outcomes in Class IV at SDN 1 Genteng, Banyuwangi, East Java. This type of research uses a quantitative approach with a quasi-experimental research method and a non-equivalent control group design. Non-probability sampling was used. The population and sample consisted of 33 students in class IV-A as the experimental class and 39 in class IV-B as the control class in SDN 1 Genteng, Banyuwangi, East Java. The data-collection instrument used a written test using multiple choices and descriptions. Data analysis techniques using SPSS Statistics 21. The study showed that problem-based learning models with chatbot AI affected learning outcomes. Other results using problem-based learning models with chatbot AI differ from those obtained using conventional models. The improved learning outcomes based on the N-Gain score of problem-based learning models with chatbot AI is 56.1545, and that of conventional models is 21.0266. Using problem-based learning models with chatbot AI is likely effective in elementary school learning.